Design and construction of smart furniture system to help to fall asleep - Gómez-Leitón, Andrés (2019)
The project consisted in developing a furniture system that sought to facilitate the conciliation of sleep in the young adult population in Costa Rica. From the problem and requirements, previously raised; an investigation was developed to determine the causes of the problem and a series of possible solutions that went hand in hand with the technology. Then possible concepts were considered taking into account all the results of the research to develop a series of proposals by concept and then, thanks to the previous requirements, a proposal was selected that met each of these plus one formal requirement. In which it was taken into account the simplicity, adaptability, constructive feasibility and design attachment to the problem to be solved. That way it was refined by the best solution which was built for a possible subsequent validation.